Karakteristik Kompetensi Komunikasi Lintas Budaya Pada Konselor Sekolah - Harlina Harlina; Ratna Sari Dewi; Sigit Dwi Sucipto (Bulletin of Counseling and Psychotherapy, 2022)
Intercultural competence is a very complex concept with many levels and perspectives. The role of cross-cultural communication competence in the school environment is very important. The existence of students from various cultural backgrounds complements cultural diversity. Cross-cultural communication competence in this study refers to the objectives of: 1) measuring students' cross-cultural communication skills in classical guidance services; and 2) knowing the level of cross-cultural communication skills possessed by students. Questionnaire measurement involves five important aspects, namely 1) Attitudes, when interacting with other people; 2) Knowledge; 3) Interpreting and associating skills; 4) Discovery and interaction skills; and 5) Critical cultural awareness. This research uses descriptive quantitative survey method. The implementation of this research at SMA/MAK Palembang city consisted of 528 subjects. The results of this study are a) cross-cultural communication competence of high school/MAK students in classical guidance services is measured using a questionnaire that has been tested for validity and reliability; and b) the level of cross-cultural communication competence of SMA/MAK students with a percentage of 57% is in the medium category.